Site-Specific Synthesis of Carbazole Derivatives through Aryl Homocoupling and Amination - Ban, Jaeyoung; Lim, Minkyung; Shabbir, Saira; Baek, Junghyun; Rhee, Hakjune (Synthesis, 2020)
We synthesized various carbazoles from anilines through a three-step process with good overall yields (up to 48%). This process comprises N-acetylation, copper(0)-mediated Ullmann homocoupling, and acid-mediated intramolecular amination. It permits various functional groups on the substrate. Scale-up of the developed three-step synthetic route to carbazoles was also demonstrated.
Keywords: N-acetylation; aryl homocoupling; Ullmann coupling reaction; Täuber carbazole synthesis; intramolecular amination